2022
DOI: 10.1001/jamanetworkopen.2022.0873
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Outcomes and Process of Care for Patients Treated at Hospitals Dedicated for COVID-19 Care vs Other Hospitals

Abstract: IMPORTANCEEarly in the SARS-CoV-2 pandemic, the M Health Fairview Hospital System established dedicated hospitals for establishing cohorts and caring for patients with COVID-19, yet the association between treatment at COVID-19-dedicated hospitals and mortality and complications is not known. OBJECTIVE To analyze the mortality rate and complications associated with treatment at the COVID-19-dedicated hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…This finding is important because evidence both before and during the COVID-19 era showed that, among patients with ARDS, oxygenation on the third day after intubation may be more strongly associated with mortality than oxygenation on the day of intubation . Also, the occurrence of bacteremia among survivors was 57.1% (8 of 14) in the full vaccination group vs 73.9% (65 of 88) in the control group, and, although statistically insignificant, this difference in occurrence might be associated with different mortality rates between groups …”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This finding is important because evidence both before and during the COVID-19 era showed that, among patients with ARDS, oxygenation on the third day after intubation may be more strongly associated with mortality than oxygenation on the day of intubation . Also, the occurrence of bacteremia among survivors was 57.1% (8 of 14) in the full vaccination group vs 73.9% (65 of 88) in the control group, and, although statistically insignificant, this difference in occurrence might be associated with different mortality rates between groups …”
Section: Discussionmentioning
confidence: 86%
“… 16 , 17 Also, the occurrence of bacteremia among survivors was 57.1% (8 of 14) in the full vaccination group vs 73.9% (65 of 88) in the control group, and, although statistically insignificant, this difference in occurrence might be associated with different mortality rates between groups. 18 …”
Section: Discussionmentioning
confidence: 99%
“…In a study in the USA, during the first 6 months of the pandemic, the mortality rates were strongly associated with the prevalence of COVID-19 in the hospital's surrounding communities, but neither the number of intensive care unit beds nor academic status was relevant [ 4 ]. Another USA report suggested that treatment at a hospital dedicated to COVID-19 care performed better in terms of the survival rates of patients with severe COVID-19 [ 5 ]. In that study, mortality rates were higher in specialized hospitals, but multivariate adjustment verified that their outcomes were better when patients' severity was accounted for.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally hospital treated participants received immunotherapy, plasma therapy, ventilator use, and steroids. It has previously been reported that significantly higher doses of corticosteroids, remdesivir, and tocilizumab have been used in patients of COVID-hospitals than non-COVID-hospitals ( 53 ). In the current study immunotherapy was only administered to severely infected patients who had received hospital treatment.…”
Section: Discussionmentioning
confidence: 99%